Automatic Calibration Using a Modified Genetic Algorithm for Millimeter-Wave Antenna Modules in MIMO Systems. (3rd June 2020) - Hu, Cheng-Nan; Lo, Philip; Ho, Chien-Peng; Chang, Dau-Chyrh
Abstract : This study proposes a method for designing and calibrating a millimeter-wave (mm-wave) multiple-input multiple-output (MIMO) antenna module. Herein, we adopt a design example involving a 64-element MIMO antenna array arranged in a triangular lattice (instead of the commonly used rectangular lattice) to achieve a 3°dB enhancement in effective isotropic radiated power. Analyzing a grating lobe diagram indicates a scan volume of ±60°/±45° in the azimuth/elevation direction. To calibrate the massive mm-wave MIMO antenna module, we propose a modified genetic algorithm to align the amplitude/phase of the transmitting/receiving signal of the module to reduce the time required for the calibration process. Finally, we conducted a simple experiment to validate the proposed method.